The Relationship of Public Mother's Knowledge about Breast Care and the Flowness of Breast Milk in the Watampone Health Center - Sulfianti, Sulfianti; Ismawati, Ismawati; Mustar, Mustar; Hasnidar, Hasnidar; Arsih, Yulia (Journal La Medihealtico, 2024)
Breast care is care that should be done to prepare the breasts so they are in good condition when breastfeeding the baby. In Indonesia, the incidence of mastitis and sore nipples in 2019 was 55% due to errors in breast care, which was found to be 46%. The incidence of postpartum mothers experiencing abscesses in Indonesia in 2019 was 10% due to low knowledge of mothers in breast care. This study aims to determine the relationship between postpartum mothers' knowledge about breast care and smooth breastfeeding at the Watampone health center. This type of research is included in Quantitative research. The type of research used is analytical observational. The population in this study were all postpartum mothers who were at the Watampone Community Health Center UPT and the total sample was 46 people. The results of this study show that of the 46 respondents with good knowledge of breast care and experiencing smooth breastfeeding, there were 10 people (21.7%), while the number of respondents with poor knowledge and experiencing non-fluent breastfeeding was 36 people (78.3%). That there is a significant relationship between knowledge of breast care and smooth breastfeeding in Postpartum mothers at the Watampone Community Health Center UPT. This was proven through Continuity Correction, p-v 549 was obtained, which means there is a relationship between mother's knowledge and smooth breastfeeding at the Watampone health center. In the Lack of Knowledge category, there were 25 people (54.4%).